PENGARUH AUDIT TENURE DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG DENGAN REPUTASI KAP SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Periode 2013-2016) - Daratika, Duma; Zirman, Zirman; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to determine the effect of audit tenure and size company, to the acceptance of Audit Report Lag with Public Accounting Firm’s Reputation as a moderate. The samples of this research are mining companies which listed on the Indonesia Stock Exchange (BEI) in 2013 to 2016. The population of this research are 37 companies. Based on purposive sampling method, the total of final samples are 148 samples. Analysis of data is carried out using multiple regression method wth the aid of SPPS version 17 computer program. The result of this research before moderating show that audit tenure and firm size are significant influence on audit report lag. And Public accounting firm’s reputation proved to moderate the effect of company size on audit report lag while Public accounting firm’s reputation do not give contribution to affect audit tenure to minimize audit report lag.Keywords : audit tenure, firm size, public accounting firm’s reputation, audit report lag.